The relationship between place management and physical environment in apartment crime - McCord, Eric Steven (2004)
The focus of this research is crime in multi-unit rental structures, Specifically, apartment complexes. It seeks to identify management policies and environmental attributes that are associated with lower crime and police calls for service rates